2008
DOI: 10.1258/jhsrp.2008.008028
|View full text |Cite
|
Sign up to set email alerts
|

Using qualitative research methods to improve recruitment to randomized controlled trials: The Quartet study

Abstract: Straightforward replication of the ProtecT complex intervention was more complicated than expected. However, the study has increased understanding of RCT recruitment and identified ways to overcome barriers to collaboration. Such research is more easily undertaken in the feasibility stage of an RCT, and greater success will be achieved if the research is integrated into the everyday conduct of RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 11 publications
(16 reference statements)
4
76
0
Order By: Relevance
“…449 Further work focused on using qualitative analysis of recruitment interviews, followed by feedback to recruiting staff in other trials to see if it could be used to improve recruitment. 450 However, difficulties relating to both logistics and acceptability limited effectiveness. de Salis and colleagues 450 found that, because the analysis and feedback process had not been included in the initial study protocol of the trials, they were faced with governance issues which made it very difficult to implement peer review quickly enough to make a difference in trials currently under way.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…449 Further work focused on using qualitative analysis of recruitment interviews, followed by feedback to recruiting staff in other trials to see if it could be used to improve recruitment. 450 However, difficulties relating to both logistics and acceptability limited effectiveness. de Salis and colleagues 450 found that, because the analysis and feedback process had not been included in the initial study protocol of the trials, they were faced with governance issues which made it very difficult to implement peer review quickly enough to make a difference in trials currently under way.…”
Section: Discussionmentioning
confidence: 99%
“…450 However, difficulties relating to both logistics and acceptability limited effectiveness. de Salis and colleagues 450 found that, because the analysis and feedback process had not been included in the initial study protocol of the trials, they were faced with governance issues which made it very difficult to implement peer review quickly enough to make a difference in trials currently under way. 450 They also found it difficult to get all members of the study team on board and to commit to the process, concluding that it was important to build it into the study protocol at the trial design stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations